Developing Countries And The Wto Dispute Resolution System: A Legal Assessment And Review - ANYIWE, LINIMOSE NZERIUNO; EKHATOR, EGHOSA OSA (Journal of Sustainable Development Law and Policy, 2025)
The aim of this paper is to review and analyse the WTO procedures and rules designed to resolve developing countries disputes. The Dispute Settlement Understanding (DSU) of the World Trade Organization is generally considered as providing innovative set of rules through which countries could address and resolve trade disputes amongst themselves. The DSU also establishes an Advisory Centre, which seeks to assist developing countries to resolve trade disputes. Despite these innovations, opinions are divided on the practical effectiveness of the DSU and the Advisory Centre, particularly with respect to resolving disputes involving developing countries. In this paper, we shall examine the practical effectiveness of DSU and the roles of the Advisory Centre in the dispute resolution processes involving developing countries. Drawing examples from previous disputes, some practical challenges and constraints with the current procedures faced by developing countries are identified and discussed; they are: lack of expertise, inability to enforce WTO rulings, reluctance to institute trade disputes and economic pressure applied by developed countries on developing countries in trade disputes amongst others. Addressing these challenges are critical to the overall success of the DSU. This paper calls for a review of the DSU to incorporate the reforms enunciated by various stakeholders to the WTO.